Preparation method of Hall electrode for high-purity germanium Hall test

Through physical surface grinding, polishing, corrosion and passivation fluid treatment, as well as the welding steps of high-temperature and low-temperature soldering irons, the problems of scratches on the surface, large thickness errors and unstable electrode contacts are solved, and the accuracy, stability and repeatability of high-purity germanium Hall tests are improved.

CN119836219AActive Publication Date: 2025-04-15安徽光智科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411965372.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the high-purity germanium Hall test, there are scratches on the surface of Hall sample, large thickness error, poor surface flatness, unstable electrode contact, and easy to cause diffusion of indium impurities, resulting in reduced accuracy and stability of Hall test results.

Method used

Surface physical grinding and polishing technology is used to eliminate surface scratches formed by single-line cutting of Hall samples, surface oxides are eliminated through corrosion of HNO3:HF and HF:water ratio and passivation liquid treatment. High- and low-temperature soldering iron welding steps are used to form Hall electrodes in regular form to avoid dummy welding and hollows.

Benefits of technology

Effectively eliminate surface scratches and thickness errors of Hall samples, improve surface flatness, enhance electrode contact stability, prevent indium impurities from diffusion, and improve the accuracy, stability and repeatability of Hall tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836219A_ABST
    Figure CN119836219A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Hall electrode for a high-purity germanium Hall test. The preparation method comprises the following steps: cutting a crystal by a single line to obtain a Hall sample wafer; pouring an aluminum oxide polishing solution on the smooth quartz plate, grinding and polishing the two surfaces of the Hall sample wafer until scratches formed by single-line cutting are eliminated, washing with deionized water, and drying with nitrogen; hall samples are respectively cut at the center and the edge of the Hall sample wafer; the method comprises the following steps: cleaning a Hall sample, corroding the Hall sample by using a corrosive liquid with the volume ratio of HNO3 to HF being (2-4): 1, soaking the Hall sample by using a passivation liquid with the volume ratio of HF to water being 1: 1, cleaning the Hall sample by using pure water, and blow-drying the Hall sample by using high-purity nitrogen; and electrode welding: preparing a high-purity indium wire, setting the high temperature of the electric soldering iron at 250-280 DEG C, firstly performing point contact on the indium wire, uniformly dotting the indium wire on the four corners of the Hall sample, setting the low temperature of the electric soldering iron at 180-210 DEG C, and sequentially spot-welding the four corners on the Hall equipment circuit board by dotting indium on the four corners to form a Hall electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of semiconductor material detection, and more specifically to a method for preparing a Hall electrode for high-purity germanium Hall test. Background Art

[0002] A voltage is applied in the length direction of the semiconductor sample and a magnetic field is applied in the width direction. Due to the effect of the magnetic field, a Lorentz force is generated in the height direction. This phenomenon is called the Hall effect. The Lorentz force causes the carriers moving in the semiconductor sample to accumulate above the semiconductor sample, thus generating an electric field on the top and bottom (height direction) of the semiconductor sample. The electric force generated by the electric field is balanced with the Lorentz force. This phenomenon is used to perform Hall detection on the semiconductor sample.

[0003] When performing low-temperature Hall detection, high requirements are placed on the sample and electrode contact, such as: the sample thickness should be uniform, the sample surface should be flat, without holes or grooves, the electrode contact position should be at the edge of the sample, the area of ​​the electrode contact point should be small enough, and the electrode contact should be stable enough.

[0004] The conventional detection method in this field is to first cut a sample with a thickness of less than 1 mm, then cut the sample into small square samples, and finally make indium electrodes at the four corners of the sample for Hall detection. For example, patent documents CN114577561A and CN114235899A both use similar methods.

[0005] The problems existing in this process at this stage include: in the sample preparation process, single-line cutting is required to sample the Hall sample, resulting in many scratches on the Hall sample, large thickness error, and poor surface flatness; the small Hall sample prepared by the Hall sample is not cleaned up during the corrosion process and the surface is prone to secondary oxidation; the Hall sample has cold solder joints and voids during the electrode welding process, resulting in unstable electrode contact, and high temperatures will cause indium impurities to diffuse into the interior of the sample, reducing the purity of the Hall sample, etc. These problems will greatly reduce the accuracy and stability of the Hall test results. Summary of the invention

[0006] In view of the problems existing in the background technology, an object of the present invention is to provide a method for preparing a Hall electrode for high-purity germanium Hall testing, which can completely eliminate the surface scratches formed by single-line cutting of the Hall sample and reduce the thickness error and roughness of the Hall sample.

[0007] Another object of the present disclosure is to provide a method for preparing a Hall electrode for high-purity germanium Hall testing, which can eliminate the oxides remaining on the surface of the Hall sample during the corrosion process, so that the surface treatment is clean, thereby ensuring the accuracy and stability of the Hall test and improving the repeatability of the Hall test.

[0008] Another object of the present disclosure is to provide a method for preparing a Hall electrode for high-purity germanium Hall test, which does not cause diffusion of indium impurities.

[0009] Thus, a preparation method of a Hall electrode for high-purity germanium Hall test includes the following steps: S1, Hall sample cutting: selecting a portion on a high-purity germanium crystal that needs to be tested for Hall, and cutting the crystal into a Hall sample in a single line perpendicular to the crystal growth axis direction, wherein the thickness of the Hall sample is (1.0±0.3) mm-(2.0±0.3) mm; S2, Hall sample surface treatment: performing physical grinding and polishing on the surface of the cut Hall sample, wherein the physical grinding and polishing adopts an alumina polishing liquid poured on a smooth quartz plate, and repeatedly grinding and polishing the double sides of the Hall sample until the Hall The surface scratches formed by the single-line cutting of the sample are finally rinsed with deionized water and dried with nitrogen. The thickness error of the Hall sample is less than 0.1mm, and the roughness of the Hall sample is less than 1μm; S3, Hall sample preparation: Hall samples are cut out at the center and edge of the Hall sample respectively. The Hall sample is a small square with a side length of (10±0.1)mm-(15±0.1)mm; S4, Hall sample cleaning treatment, including sub-steps: S41, corrosion: prepare a corrosion solution with a volume ratio of HNO3:HF=(2-4):1, and place the Hall sample in the corrosion solution for corrosion 2-4min, until relatively strong yellow smoke is produced, S42, passivation: prepare a passivation solution with a volume ratio of HF: water = 1:1, take out the Hall sample that has been corroded from the corrosion solution, and quickly put it into the passivation solution and soak it for 5-10min, S43, pure water cleaning: take out the passivated Hall sample from the passivation solution, rinse the Hall sample with pure water, and the rinsing time is not less than 15min, S44, blow dry: finally use high-purity nitrogen to blow dry; S5, welding electrode: welding electrode is carried out in two steps; S51, Hall sample point indium: prepare high-purity indium wire, use The electric soldering iron is set at a high temperature of 250-280°C, first point-contacting the indium wire, and then evenly spotting the molten indium wire on the four corners of the Hall sample, and controlling the contact time between the electric soldering iron and the Hall sample to be as short as possible. S52, spot welding the Hall sample on the Hall device circuit board: the electric soldering iron is set at a low temperature of 180-210°C, and the indium on the four corners of the Hall sample is spot-welded in turn on the Hall device circuit board by using the melting and resolidification of indium. The spot welding process requires meticulousness and multiple times, and each corner is controlled to avoid the existence of cold solder joints and voids to form a Hall electrode. The beneficial effects of the present disclosure are as follows.

[0010] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, after the Hall sample is cut out by single-line cutting in step S1, the surface physical grinding and polishing in step S2 is performed to completely eliminate the surface scratches formed by the single-line cutting of the Hall sample, thereby reducing the thickness error and roughness of the Hall sample, thereby improving the accuracy and stability of the Hall test, and improving the repeatability of the Hall test.

[0011] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, in the surface treatment of the Hall sample in step S4, it is first corroded by a corrosive solution with a volume ratio of HNO3:HF=(2-4):1 in sub-step S41, and then passivated by a passivation solution with a volume ratio of HF:water=1:1, which can fully eliminate the oxides remaining on the surface of the Hall sample during the corrosion process, making the surface treatment clean, and a hydrophobic layer (H end) is generated on the surface of the Hall sample, which can prevent the secondary oxidation of germanium, ensure the original performance of germanium, ensure the accuracy and stability of the Hall test, and improve the repeatability of the Hall test.

[0012] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, in the welding electrode of step S5: first, a high temperature of 250-280°C is used in the indium of the Hall sample point in sub-step S51. At the high temperature, the indium wire will melt quickly and solidify regularly at the four corners of the Hall sample, so that the contact points of the four Hall electrodes are uniform in size and shape, and the contact between the soldering iron and the Hall sample is as short as possible, reducing the risk of indium impurity diffusion; then in sub-step S52, the Hall sample is spot welded on the Hall device circuit board at a low temperature of 180-210°C, which will not cause the diffusion of indium impurities and protect the original performance of the Hall sample. Because the spot welding process is required to be meticulous and performed multiple times, each corner is controlled to avoid the existence of cold solder joints and voids, thereby effectively avoiding cold solder joints and voids, so that the prepared Hall electrode contact is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic flow chart of the process of making Hall samples from high-purity germanium crystals.

[0014] Figure 2 It is a surface morphology diagram of the Hall sample before surface treatment measured by the 3D profilometer of Example 1. The left figure is a stereoscopic diagram, and the right figure is a top view.

[0015] Figure 3 It is a surface morphology diagram of the Hall sample after surface treatment measured by the 3D profilometer of Example 1. The left figure is a stereoscopic diagram, and the right figure is a top view. DETAILED DESCRIPTION

[0016] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0017] [Preparation method of Hall electrode for high purity germanium Hall test]

[0018] Reference Figure 1 According to the present disclosure, the preparation method of the Hall electrode for high-purity germanium Hall test comprises the following steps:

[0019] S1, Hall sample cutting: select the part that needs to be tested on the high purity germanium crystal, and cut the crystal into Hall samples in a single line perpendicular to the crystal growth axis. The thickness of the Hall sample is (1.0±0.3)mm-(2.0±0.3)mm;

[0020] S2, surface treatment of Hall samples: the cut Hall samples are subjected to physical grinding and polishing. Physical grinding and polishing uses alumina polishing liquid poured on a smooth quartz plate. The double sides of the Hall sample are repeatedly ground and polished until the surface scratches formed by the single-line cutting of the Hall sample are completely eliminated. Finally, it is rinsed with deionized water and dried with nitrogen. The thickness error of the Hall sample is less than 0.1mm, and the roughness of the Hall sample is less than 1μm;

[0021] S3, Hall sample preparation: Hall samples are cut out at the center and edge of the Hall sample. The Hall sample is a small square with a side length of (10±0.1) mm-(15±0.1) mm;

[0022] S4, Hall sample cleaning process, including sub-steps:

[0023] S41, corrosion: prepare a corrosion solution with a volume ratio of HNO3:HF=(2-4):1, place the Hall sample in the corrosion solution and corrode for 2-4 minutes until strong yellow smoke is produced;

[0024] S42, passivation: prepare a passivation solution with a volume ratio of HF: water = 1:1, take out the Hall sample that has been corroded from the corrosive solution, and quickly put it into the passivation solution and soak it for 5-10 minutes;

[0025] S43, pure water cleaning: take out the passivated Hall sample from the passivation solution, and rinse the Hall sample with pure water for no less than 15 minutes;

[0026] S44, Blow Dry: Finally, use high-purity nitrogen to blow dry;

[0027] S5, welding electrode: welding electrode is performed in two sub-steps;

[0028] S51, Hall sample indium point: prepare high-purity indium wire, set the electric soldering iron to a high temperature of 250-280℃, first touch the indium wire, then evenly point the molten indium wire on the four corners of the Hall sample, and control

[0029] The contact time between the soldering iron and the Hall sample should be as short as possible;

[0030] S52, spot welding of the Hall sample on the Hall device circuit board: Set the electric soldering iron to a low temperature of 180-210°C, and spot weld the four corners of the Hall sample on the Hall device circuit board in turn by tapping the indium on the four corners of the Hall sample. Using the melting and resolidification of indium, the spot welding process requires meticulousness and multiple times to control each corner to avoid cold solder joints and voids, so as to form a Hall electrode.

[0031] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, after the Hall sample is cut out by single-line cutting in step S1, the surface physical grinding and polishing in step S2 is performed to completely eliminate the surface scratches formed by the single-line cutting of the Hall sample, thereby reducing the thickness error and roughness of the Hall sample, thereby improving the accuracy and stability of the Hall test, and improving the repeatability of the Hall test.

[0032] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, in the surface treatment of the Hall sample in step S4, it is first corroded by a corrosive solution with a volume ratio of HNO3:HF=(2-4):1 in sub-step S41, and then passivated by a passivation solution with a volume ratio of HF:water=1:1, which can fully eliminate the oxides remaining on the surface of the Hall sample during the corrosion process, making the surface treatment clean, and a hydrophobic layer (H end) is generated on the surface of the Hall sample, which can prevent the secondary oxidation of germanium, ensure the original performance of germanium, ensure the accuracy and stability of the Hall test, and improve the repeatability of the Hall test.

[0033] In the preparation method of the Hall electrode for high-purity germanium Hall test according to the present disclosure, in the welding electrode of step S5: first, a high temperature of 250-280°C is used in the indium of the Hall sample point in sub-step S51. At the high temperature, the indium wire will melt quickly and solidify regularly at the four corners of the Hall sample, so that the contact points of the four Hall electrodes are uniform in size and shape, and the contact between the soldering iron and the Hall sample is as short as possible, reducing the risk of indium impurity diffusion; then in sub-step S52, the Hall sample is spot welded on the Hall device circuit board at a low temperature of 180-210°C, which will not cause the diffusion of indium impurities and protect the original performance of the Hall sample. Because the spot welding process is required to be meticulous and performed multiple times, each corner is controlled to avoid the existence of cold solder joints and voids, thereby effectively avoiding cold solder joints and voids, so that the prepared Hall electrode contact is stable.

[0034] In step S1, for example, single wire cutting uses a diamond wire with a diameter of 0.4-0.8 mm. In step S1, for example, the thickness of the Hall sample is 1.5 mm.

[0035] In step S2, in one example, a suspension of aluminum oxide and water is prepared as a grinding and polishing liquid, the particle size of aluminum oxide is 10-20 μm, and the weight ratio of aluminum oxide to water is (15-25): 100. In step S2, for example, the purity of nitrogen is 9N.

[0036] In step S3, in one example, the Hall sample is a small square with a side length of 12 mm.

[0037] In sub-step S41, in one example, a corrosion solution with a volume ratio of HNO3:HF=3:1 is prepared, and the corrosion is carried out for 3 minutes. In sub-step S42, in one example, the immersion is carried out for 8 minutes. In sub-step S43, in one example, the flushing time is 20-30 minutes. For example, the flushing time is 25 minutes. In sub-step S44, for example, the purity of nitrogen is 9N.

[0038] In sub-step S51, for example, the purity of the high-purity indium wire is above 5N. In sub-step S51, in one example, the electric soldering iron is set to a high temperature of 270° C. In sub-step S52, in one example, the electric soldering iron is set to a low temperature of 195° C.

[0039] [test]

[0040] Example 1

[0041] The preparation method of the Hall electrode for high-purity germanium Hall test of Example 1 adopts the following steps:

[0042] S1, Hall sample cutting: select the part that needs to be tested on the high-purity germanium crystal, and use a diamond wire with a diameter of 0.6mm to cut the crystal into a Hall sample perpendicular to the crystal growth axis. The thickness of the Hall sample is 1.5mm.

[0043] S2, surface treatment of Hall sample: the cut Hall sample is subjected to physical grinding and polishing on the surface, and a suspension of aluminum oxide and water is prepared as a grinding and polishing liquid. The particle size of aluminum oxide is 15μm, and the weight ratio of aluminum oxide to water is 20:100. The physical grinding and polishing adopts aluminum oxide polishing liquid poured on a smooth quartz plate, and the double-sided Hall sample is repeatedly ground and polished until the surface scratches formed by the single-line cutting of the Hall sample are completely eliminated. Finally, it is rinsed with deionized water and blown dry with nitrogen gas of purity 9N. The thickness error of the Hall sample is less than 0.1mm, and the roughness of the Hall sample is less than 1μm;

[0044] S3, Hall sample preparation: Hall samples are cut out at the center and edge of the Hall sample. The Hall sample is a small square with a side length of 12 mm.

[0045] S4, Hall sample cleaning process, using the following sub-steps:

[0046] S41, corrosion: prepare a corrosion solution with a volume ratio of HNO3:HF=3:1, place the Hall sample in the corrosion solution and corrode for 3 minutes until strong yellow smoke is produced;

[0047] S42, passivation: prepare a passivation solution with a volume ratio of HF: water = 1:1, take out the Hall sample that has been corroded from the corrosive solution, and quickly put it into the passivation solution and soak it for 8 minutes;

[0048] S43, pure water cleaning: take out the passivated Hall sample from the passivation solution, and rinse the Hall sample with pure water for 25 minutes;

[0049] S44, blow dry: Finally, use high-purity nitrogen with a purity of 9N to blow dry;

[0050] S5, welding electrode: welding electrode is performed in two sub-steps;

[0051] S51, Hall sample indium point: prepare a high purity indium wire with a purity of 5N, set the electric soldering iron to a high temperature of 270℃, first touch the indium wire, and then evenly touch the molten indium wire on the four sides of the Hall sample.

[0052] At each corner, control the contact time between the soldering iron and the Hall sample to be as short as possible;

[0053] S52, spot welding of the Hall sample on the Hall device circuit board: Set the soldering iron to a low temperature of 195°C, and spot weld the four corners of the Hall sample on the Hall device circuit board in turn by touching the indium on the four corners of the Hall sample. The spot welding process requires meticulousness and must be performed multiple times to control each corner to avoid cold solder joints and voids, so as to form a Hall electrode.

[0054] Comparative Example 1

[0055] Except that the surface treatment of the Hall sample in step S2 is not performed, the rest is the same as in Example 1.

[0056] Comparative Example 2

[0057] Except that the passivation of sub-step S42 is not performed in the Hall sample cleaning process of step S4, and the "take out the passivated Hall sample from the passivation solution" in step S43 is changed to "take out the corroded Hall sample from the corrosive solution", the rest is the same as Example 1.

[0058] Comparative Example 3

[0059] Except that in the sub-step S52 of welding the electrodes in step S5, "setting the low temperature of the electric soldering iron to 195° C." is modified to "setting the high temperature of the electric soldering iron to 270° C.", the rest is the same as in embodiment 1.

[0060] Comparative Example 4

[0061] Except that in the sub-step S51 of welding the electrodes in step S5, "setting the high temperature of the electric soldering iron to 270° C." is modified to "setting the low temperature of the electric soldering iron to 195° C.", the rest is the same as in embodiment 1.

[0062] For the same cross section of the same crystal, five Hall samples (A, B, C, D, E) were taken in Example 1 and Comparative Examples 1-4, and Hall electrodes were prepared using the preparation methods of Example 1 and Comparative Examples 1-4, respectively. Each Hall electrode was tested 4 times. The carrier concentration and type were detected by HL9900 of Toho Technology, USA.

[0063] Table 1 Hall test results of Example 1 and Comparative Examples 1-4

[0064]

[0065]

[0066] From the comparison of the four test deviations of Example 1 and Comparative Example 1, it can be seen that Example 1 significantly improves the accuracy and stability of the Hall test results by adopting the Hall sample surface treatment process in step S2.

[0067] From the average values ​​of the carrier concentrations of the four tests and the four test deviations of Example 1 and Comparative Example 2, it can be seen that by immersing Example 1 in the passivation solution after corrosion, the accuracy and stability of the Hall test results can be improved, and the test repeatability can be improved. The reason is that the oxides remaining on the surface of the sample during the corrosion process are fully eliminated, and a hydrophobic layer (H end) is generated on the surface of the germanium to prevent the secondary oxidation of germanium, thereby ensuring the original performance of the germanium sheet.

[0068] From the average values ​​of the carrier concentrations of the four tests in Example 1 and Comparative Example 3, it can be seen that Comparative Example 3 only uses a single high-temperature setting. After the high-temperature soldering iron is in contact with the Hall sample for a long time, indium impurity diffusion occurs, and the accuracy of the sample is greatly affected.

[0069] From the four test deviations of Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 only adopts a single low-temperature setting. During the welding process of the low-temperature soldering iron, the four corners of the sample solidify irregularly, making the size and shape of the four electrode contact points uneven, and the stability and accuracy of the Hall test results are affected.

[0070] also, Figure 2 and Figure 3Photos of the Hall sample of Example 1 before and after the processing in step S2 are given. Figure 2 It is a surface morphology diagram of the Hall sample before surface treatment measured by the 3D profilometer of Example 1. The left figure is a stereoscopic diagram, and the right figure is a top view. Figure 3 It is a surface morphology diagram of the Hall sample after surface treatment measured by the 3D profilometer of Example 1. The left figure is a stereoscopic diagram, and the right figure is a top view. Figure 2 Obvious linear bumps can be seen. Figure 3 The sample surface is flat and has low roughness.

[0071] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A method for preparing a Hall electrode for high-purity germanium Hall test, characterized in that: Includes steps: S1, Hall sample cutting: select the part that needs to be tested on the high purity germanium crystal, and cut the crystal into Hall samples in a single line perpendicular to the crystal growth axis. The thickness of the Hall sample is (1.0±0.3)mm-(2.0±0.3)mm; S2, surface treatment of Hall samples: the cut Hall samples are subjected to physical grinding and polishing. Physical grinding and polishing uses alumina polishing liquid poured on a smooth quartz plate. The double sides of the Hall sample are repeatedly ground and polished until the surface scratches formed by the single-line cutting of the Hall sample are completely eliminated. Finally, it is rinsed with deionized water and dried with nitrogen. The thickness error of the Hall sample is less than 0.1mm, and the roughness of the Hall sample is less than 1μm; S3, Hall sample preparation: Hall samples are cut out at the center and edge of the Hall sample. The Hall sample is a small square with a side length of (10±0.1) mm-(15±0.1) mm; S4, Hall sample cleaning process, including sub-steps: S41, corrosion: prepare a corrosion solution with a volume ratio of HNO3:HF=(2-4):1, place the Hall sample in the corrosion solution and corrode for 2-4 minutes until strong yellow smoke is produced; S42, passivation: prepare a passivation solution with a volume ratio of HF: water = 1:1, take out the Hall sample that has been corroded from the corrosive solution, and quickly put it into the passivation solution and soak it for 5-10 minutes; S43, pure water cleaning: take out the passivated Hall sample from the passivation solution, and rinse the Hall sample with pure water for no less than 15 minutes; S44, Blow Dry: Finally, use high-purity nitrogen to blow dry; S5, welding electrode: welding electrode is performed in two sub-steps; S51, Hall sample point indium: prepare high-purity indium wire, set the electric soldering iron to a high temperature of 250-280℃, first touch the indium wire, then evenly touch the molten indium wire on the four corners of the Hall sample, and control the contact time between the electric soldering iron and the Hall sample to be as short as possible; S52, spot welding of Hall sample on Hall device circuit board: Set the soldering iron to a low temperature of 180-210℃, and solder the indium on the four corners of the Hall sample, using the melting and resolidification of indium. The four corners of the Hall sample are spot welded on the Hall device circuit board in sequence. The spot welding process requires meticulousness and multiple times to control each corner to avoid cold solder joints and voids to form Hall electrodes.

2. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In step S1, single wire cutting uses a diamond wire with a diameter of 0.4-0.8 mm; and / or In step S1 , the thickness of the Hall sample is 1.5 mm.

3. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In step S2, a suspension of aluminum oxide and water is prepared as a grinding and polishing liquid, the particle size of the aluminum oxide is 10-20 μm, and the weight ratio of aluminum oxide to water is (15-25):

100.

4. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In step S2, the purity of nitrogen is 9N.

5. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In step S3, the Hall sample is a small square with a side length of 12 mm.

6. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In sub-step S41, a corrosion solution with a volume ratio of HNO3:HF=3:1 is prepared and the corrosion is carried out for 3 minutes; and / or In sub-step S42, soak for 8 minutes.

7. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In sub-step S43, the flushing time is 20-30 minutes.

8. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 7, characterized in that: In sub-step S43, the flushing time is 25 minutes.

9. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In sub-step S44, the purity of nitrogen is 9N.

10. The method for preparing a Hall electrode for high-purity germanium Hall test according to claim 1, characterized in that: In sub-step S51, the purity of the high-purity indium wire is 5N or above; and / or In sub-step S51, the electric soldering iron is set to a high temperature of 270° C.; and / or In sub-step S52, the electric soldering iron is set to a low temperature of 195°C.

Citation Information

Patent Citations

  • Novel Hall test method

    CN103794526A

  • Method for detecting carrier concentration of high-purity germanium polycrystal

    CN114355137A

  • Miniature probe station for Hall test of high-purity germanium single crystal and test method

    CN116087571A

  • Flexible Hall sensing device based on graphene crossed nano-strips

    CN117939999A

  • SEMICONDUCTOR DEVICE and MANUFACTURING METHOD OF SEMICONDUCTOR DEVICE

    US20220223785A1